FRI0133 Evaluation of the use of the cardiovascular risk score tables in patients with rheumatoid arthritis. (23rd January 2014) - Paredes, S.P.; Taverner, D.; Llop, C.; Gomez, D.
Abstract : Background: Patients with rheumatoid arthritis (RA) have a higher cardiovascular risk (CVR) than the general population. This increase of the CVR is comparably equal to the CVR increase observed in type 2 diabetic patients. Objectives: The primary objective of the study was to determine the CVR of a cohort of RA patients by using the SCORE guide tables and its modification parameters according the EULAR consensus. A secondary objective of the study was to evaluate the level of hypolipidemic treatment of patients meeting both requirements of high CVR as well as total cholesterol blood levels over 200 mg/dL. Methods: This is a retrospective transversal study including patients with RA controled by the Rheumatology Department of the Hospital Universitario Sant Joan de Reus. Both clinical and analytical data needed to determine the CVR according to the SCORE tables (calibrated for Spain) were registered throughout the second semester of 2010. EULAR criteria was used for the calculation of the modified risk. It is recommended to multiply by 1.5 points the estimaded primary CVR if two of these three criteria are given: 1.- RA evolution over 10 years; 2.- Positive rheumatoid factor (RF) or anti-cyclic citrullinated peptide (anti-CCP) antibodies; 3.- Extra-articular signs. Results: The subjected population included 139 RA patients (70.5% women) with a median age of 60 years-old (SD 13.5). RF was positive in 77% of the cases, 88.4% were positive on anti-CCP antibodies, and 13.7% of the patients presented extra-articular signs. Average evolution time was 9.9 years (SD 7.6). Out of the total cohort of patients, 11 were diabetic, 48 had hypertension and 15 patients were dyslipemic. 8 cases had two CVR factors and 4 cases had three CVR factors. 15.8% were smokers and 10% were ex-smokers. 13 patients (9.35%) had a previous cardiovascular (CV) event. After excluding patients with previous CV episodes or diabetes, the sample size was reduced to 116 patientes. The median CVR calculated according to the SCORE tables was 2.19 (SD 2.58; range 0-17). 18 patients (11.3%) had a CVR score higher than 5. When EULAR modification were applied, than the average CVR was 3.32 (SD 3.9; range 0-25), and 22 patients (19%) had a CVR over 5. Out of this reduced sample group, 19 of these selected patients had not been receiving any hypolipidemic treatment although 11 of them (9.5% of the total sample) presented total cholesterol blood levels over 200 mg/dL. Conclusions: In our RA sample population the percentage of patients with previous CV disease is similar to the described in the literature. The application of the proposed corrections by the EULAR consensus in the CVR calculation through the SCORE tables increases in a relevant way the percentage of the considered CV high risk patients. In our patients with high CVR and high total cholesterol blood levels was observed that nearly 10% of these were not receiving any hypolipidemic treatment. Taking into account the high morbidity and mortality described in this patients due to CV causes, rheumatologists should have an effective influence in the dyslipidemia control as an independent risk factor of the CV disease References: Van Halm VP, Peters MJ, Voskuyl AE, et al. Rheumatoid arthritis versus diabetes as a risk factor for cardiovascular disease: a cross-sectionalstudy, the CARRE investigation: Ann Rheum Dis 2009; 68: 1395-1400. Disclosure of Interest: None Declared